The Effect of Constructive Play Therapy on Anxiety Levels of Preschool Children Due to Hospitalization - Nurwulansari Nurwulansari; Maria Ulfah Ashar; Huriati Huriati; Sysnawati Syarif (Journal of Health Science and Prevention, 2019)
During the hospitalization process, the child will show anxiety due to unfamiliar environmental factors, lack of freedom in activities, and lack of emotional support. Continual anxiety will cause a decrease in the immune system so that it accelerates the occurrence of disease complications during treatment and slows down the recovery process. The focus of nursing intervention that is done is to minimize anxiety by providing psychological support to children through the provision of constructive play therapy. The aim if this research is to determine the effect of constructive play therapy towards the anxiety level of preschool children due to hospitalization. The research design used in this study was Pre-experiment with a one-group pre-post test design. Data collection using preschool anxiety scale (PAS) questionnaire. The sample in this study were 30 respondents selected by using accidental sampling technique. Based on the results of the Wilcoxon Test analysis, the mean value of pre-test 36.57 and post-test 28.23 and the value of p = 0.0001 <0.05. Meaning that there is an effect of constructive play therapy on the level of anxiety in preschool children with the treatment of constructive play therapy your child who easily communicate the right feeling of anxiety during in the hospitalization, so that the anxiety experienced can be decreased. Constructive play therapy can reduce response anxiety in preschool children who experience hospitalization. Therefore, it is recommended to the hospital and nurses to be able to apply constructive play therapy. as one of the interventions to minimize the impact of hospitalization.